Optimización de la hidrofilicidad de soportes [scaffolds] de PHB y PHBV para el crecimiento de tejido biológico. - Arenas, Claudio Daniel (Instituto Sabato, 2009)
Tissue engineering has been growing as a multidisciplinary activity that combines Biology, Materials Science and Surgical reconstruction in order to provide products that restore, support or improve the usual functions of damaged organs or tissue of the human body. The main goal for the development of natural tissues has been not only the replacement of damaged ones but also the production of prosthesis made of structural materials. There are three different pathways to generate human tissues: 1) infusion of isolated or substitutive cells; 2)use of materials that induce the growth of the tissue; 3) implant of scaffold that will support the growth of the desired tissue, that may be implanted before or after cell seeding. The development of scaffolds to support the growing of tissue is a topic of major interest to the Material Science. Besides being suitable for the growth and proliferation of cells, the scaffolds must be bioabsorbable, this means that they must degradate in no-toxic substances to the body. Polyhydroxyalcanoates [PHAs] are a kind of biodegradable polyesters produced by bacterial fermentation; the first discovered PHA was polyhydroxybutyrate [PHB], a biopolymer suitable for medical applications because it degrades to butyric acid, a substance that is present in the body. It has a high melting point [~ 180 C degrees] and high crystallinity. Its mechanical properties are similar to those of isotactic polypropylene and depend on the morphology of the specimen. Also poly[hydroxybutyrate-co-hydroxyvalerate][PHBV] is another bioabsorbable PHA, with better mechanical behaviour than PHB due to its low crystallinity. The possibility to use these polymers for scaffolds is limited by their low wettability, which reduces their capacity to allow the growth and proliferation of cells. Wettability of polymers is related to the presence of polar groups on the surface, since these groups can promote chemical bonds with water. For PHB or PHBV, the contact angle is about 82 C degrees, which is very high to allow the growing the cells. One method to improve the wettability [decrease of the contact angle] of polymers, in particular of PHA, is the plasma treatment of the surface with a particular gas [N2, O2, NH3, AR]. Even when this treatment significantly reduces the contact angle, a "hydrophobic recuperation" or "aging" of the surface has been observed in many polymers submitted to different plasma treatments and stored in different environments. Thus, the main goal of this work has been to study changes in the wettability of PHB and PHBV samples produced by compression moulding, submitted to plasma of oxygen, nitrogen and air and stored in water or air at two temperatures: 4 and 25 C degrees.XPS [Photoelectronic Spectroscopy X rays] allows to determine the chemical groups present on the surface of the pristine samples as well as after the plasma treatment and during the hydrophobic recovery; X-ray spectroscopy was used to get the grade of crystallinity, AFM [Atomic Force Microscopy] to know the superficial roughness, SEM [Scanning Electronic Microscopy] to get evidence of the morphology of the surface and optical microscopy with polarized light to see the formation of spherulites in the scaffolds.The morphology that reduces the aging effect is that of PHN samples cooled in liquid nitrogen, that is, the sample with higher amorphous fraction. The treatment that enhances the wettability of the scaffold is the air plasma treatment and the environment that reduces the aging effect was the storage in water to 25 C degress, because it promotes the hydrolysis of the polyester molecules on the surface.